The contribution of undiagnosed adrenal insufficiency to euvolaemic hyponatraemia: results of a large prospective single‐centre study. (12th July 2016) - Cuesta, Martín; Garrahy, Aoife; Slattery, David; Gupta, Saket; Hannon, Anne Marie; Forde, Hannah; McGurren, Karen; Sherlock, Mark; Tormey, William; Thompson, Christopher J.
Summary: Objective: The syndrome of inappropriate antidiuresis (SIAD) is the commonest cause of hyponatraemia. Data on SIAD are mainly derived from retrospective studies, often with poor ascertainment of the minimum criteria for the correct diagnosis. Reliable data on the incidence of adrenal failure in SIAD are therefore unavailable. The aim of the study was to describe the aetiology of SIAD and in particular to define the prevalence of undiagnosed adrenal insufficiency. Design: Prospective, single centre, noninterventional, observational study of patients admitted to Beaumont Hospital with euvolaemic hyponatraemia (plasma sodium ≤ 130 mmol/l) between January 1st and October 1st 2015. Patients: A total of 1323 admissions with hyponatraemia were prospectively evaluated; 576 had euvolaemic hyponatraemia, with 573 (43·4%) initially classified as SIAD. Main outcome measures: (i) Aetiology of SIAD, defined by diagnostic criteria; (ii) Incidence of adrenal insufficiency. Results: Central nervous system diseases were the commonest cause of SIAD ( n  =   148, 26%) followed by pulmonary diseases ( n  =   111, 19%), malignancy ( n  =   105, 18%) and drugs ( n  =   47, 8%). A total of 22 patients (3·8%), initially diagnosed as SIAD, were reclassified as secondary adrenal insufficiency on the basis of cortisol measurements and clinical presentation; 9/22 cases had undiagnosed hypopituitarism; 13/22 patients had secondary adrenal insufficiency due to exogenous steroid administration. Conclusions: In a large, prospective and well‐defined cohort of euvolaemic hyponatraemia, undiagnosed secondary adrenal insufficiency co‐occurred in 3·8% of cases initially diagnosed as SIAD. Undiagnosed pituitary disease was responsible for 1·5% of cases presenting as euvolaemic hyponatraemia.